Food Choice Application (FCA): An interactive tablet application for capturing diversity of food choice - CGIAR Research Program on Rice (2020)
The FCA has been successfully implemented in behavioral experiments to capture diversity and drivers of food choice of low-middle income households in eastern India and their response to behavioral change communication. It can be used and further refined by research organizations, policy makers and nutritionists to develop healthier diets.